2015
DOI: 10.1007/s00253-015-7207-8
|View full text |Cite
|
Sign up to set email alerts
|

Significance of wood extractives for wood bonding

Abstract: Wood contains primary extractives, which are present in all woods, and secondary extractives, which are confined in certain wood species. Extractives in wood play a major role in wood-bonding processes, as they can contribute to or determine the bonding relevant properties of wood such as acidity and wettability. Therefore, extractives play an immanent role in bonding of wood chips and wood fibres with common synthetic adhesives such as urea-formaldehyde-resins (UF-resins) and phenol-formaldehyde-resins (PF-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 10 publications
0
35
0
Order By: Relevance
“…Therefore, such species are subject of increasing interest in various fields such as pharmaceuticals, leather tanning, cosmetics, and the food industry [7][8][9][10][11]. Low-molecular-weight hydroxybenzoic acids and some of their derivatives can be obtained from wood extractives and via induced lignin degradation [12,13]. Lignin is a phenolic high-molecular-mass biopolymer, composed of a highly branched phenylpropanoid framework based on the three monomers coumaryl, coniferyl, and sinapyl alcohol.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, such species are subject of increasing interest in various fields such as pharmaceuticals, leather tanning, cosmetics, and the food industry [7][8][9][10][11]. Low-molecular-weight hydroxybenzoic acids and some of their derivatives can be obtained from wood extractives and via induced lignin degradation [12,13]. Lignin is a phenolic high-molecular-mass biopolymer, composed of a highly branched phenylpropanoid framework based on the three monomers coumaryl, coniferyl, and sinapyl alcohol.…”
Section: Introductionmentioning
confidence: 99%
“…In P3, where the hardener amount was beyond the optimum, a loose structure in the cross-section also occurred. This phenomenon results from the rapid curing of the adhesive with an excess of acidic hardener and subsequent deterioration of the bond line by acid upon storage [1,5]. In the case of the oak panels (Table 4), it was difficult to observe any significant differences in the structure or thickness of the three boards, regardless of the hardener amount.…”
Section: Abc Effectmentioning
confidence: 99%
“…The chemical properties of wood and wood extractives, such as pH value and buffering capacity, are considered prime factors in bonding [5]. The gel time of a urea-formaldehyde (UF) resin strongly depends on the acidity of the wood substrate which is associated with the content of the wood extractives [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…However, the energy consumption of heat treatment in the wood industry is high, and it can cause other drawbacks including the change of surface color and decrease of mechanical strength [10]. As another effective method, extraction is often used to modify wood chemical properties, and affects wood thermal stability [11], cementing [12,13], and antibacterial properties [14]. Studies have shown that wood VOCs mainly originate from their extraction [15].…”
Section: Introductionmentioning
confidence: 99%